Convergence of more Moore, more than Moore and beyond Moore : materials, devices, and nanosystems - Deleonibus, Simon (Singapore : Jenny Stanford Publishing, 2020)
The era of Sustainable and Energy Efficient Nanoelectronics and Nanosystems has come. The research and development on Scalable and 3D integrated Diversified functions together with new computing architectures is in full swing. Besides data processing, data storage, new sensing modes and communication capabilities need the revision of process architecture to enable the Heterogeneous co integration of add-on devices with CMOS: the new defined functions and paradigms open the way to Augmented Nanosystems. The choices for future breakthroughs will request the study of new devices, circuits and computing architectures and to take new unexplored paths including as well new materials and integration schmes. This book reviews in two sections, including seven chapters, essential modules to build Diversified Nanosystems based on Nanoelectronics and finally how they pave the way to the definition of Nanofunctions for Augmented Nanosystems.
Part 1: From Nanoelectronics to Diversified Nanosystems 1. The Era of Sustainable and Energy Efficient Nanoelectronics and Nanosystems Simon Deleonibus 2. From 2D to 3D Nonvolatile Memories Akira Goda 3. Three-dimensional (3D) Vertical RRAM Qing Luo, Ming Liu 4. SOI Technologies for RF and Millimeter Wave Applications Martin Rack and Jean-Pierre Raskin Part 2: Nanofunctions for Augmented Nanosystems 5. Graphene nanoelectromechanical (NEM) switch: ultimate downscaled NEM actuators to single molecule and zeptogram mass sensors Manoharan Muruganathan and Hiroshi Mizuta 6. Self-powered 3D Nanosensor Systems for Mechanical Interfacing Applications Wenzhuo Wu and Zhong Lin Wang 7.Miniaturization and packaging of implantable biomedical silicon devices Jean-Charles Souriau
OCLC-licensed vendor bibliographic record.
Keywords: Nanotechnology; Nanoelectronics; Nanostructured materials; SCIENCE / Nanostructures; SCIENCE / Physics; SCIENCE / Life Sciences / General